1984
DOI: 10.1063/1.334094
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of radiation-induced interface traps on gate Al thickness in metal/SiO2/Si structures

Abstract: Generation of interface traps by ionizing radiation at the Si interface of an Al/SiO2/Si structure has been studied for Al thicknesses in the 500–13000 Å range for devices both with and without post-metal-anneal (PMA) treatment. In parallel with that, the interfacial stresses have been determined for the same structures by means of a laser beam reflection technique. The generation of radiation-induced interface traps, as well as the interfacial stresses, depend strongly on Al thickness and PMA treatment. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The authors have reported that the reduction of mechanical stress in gate polysilicon film is an essential aspect of suppressing Manuscript dislocations at the gate edge [1], [2]. Worsened reliability because of the increase in mechanical stress in the oxide has been reported [3], [4]. Such problems have conventionally been solved by trial and error.…”
Section: Introductionmentioning
confidence: 97%
“…The authors have reported that the reduction of mechanical stress in gate polysilicon film is an essential aspect of suppressing Manuscript dislocations at the gate edge [1], [2]. Worsened reliability because of the increase in mechanical stress in the oxide has been reported [3], [4]. Such problems have conventionally been solved by trial and error.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the oxidation process accounts for the magnitude of such a gradient, which is related to the observed dependencies of the radiation sensitivity. 10 Thus, radiation seems to be an effective way to determine the extent of stress within the MOS structure. The stressed samples in this work were also subjected to receive Co-60 irradiation, and an interesting observation of the radiation hardness behavior for an exteriorly compressed sample is shown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mechanical stress which is induced by the gate dielectrics 6 influences the interface trap density, causing a threshold voltage shift, 7 increasing the cumulative failure rate of time-dependent dielectric breakdown. 8 Ma and co-workers studied the dependencies of radiation-induced 9 and hot carrier-induced effects 10 on the thickness of gate Al in MOS capacitors. However, the relationship between the substrate injection current (J sub ) and the thickness of gate Al of MOS capacitors is still unknown.…”
mentioning
confidence: 99%
“…For a certain oxide thickness, the Si wafer is generally under tensile stress. After the gate Al deposition, if the Al film is sufficiently thick, the chip curvature changes from convex to concave, 9 as shown by the schematic diagram in Fig. 5, such that the silicon wafer is now under compressive stress.…”
mentioning
confidence: 99%